Psychological Attributes in Future Spaceport Concepts. (September 2022) - Cortelli, Rosemary; Weger, Kristin; Mesmer, Bryan
Private U.S. companies are beginning the development of earth-based spaceports-sites for launching and receiving spacecraft. Existing research has examined individuals' preferences for space travel, but not in the context of spaceports. We developed a mixed-method study that utilized qualitative and quantitative data to examine the psychological principles for founding a human factors perspective of spaceports and space habitats. We administered a survey to community members ( N = 204) to address closed and open-ended questions on general space travel, training, and team composition. After evaluating several chi square tests, we found a need for training regardless of space travel affinity, participants desired extensive training times, and participants preferred team compositions resembling existing NASA astronaut crews. These findings have implications for design and implementation of future spaceports. Further research is needed to expand the existing concepts of spaceport development, but consideration of training and team composition for commercial space travelers is necessary.